Magical Realism in Gareth Brown’s "The Book of Doors": Realisme Magis dalam The Book of Doors karya Gareth Brown - Putri, Yulia Eka; Rahayu, Anik Cahyaning (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study discusses the presence of magical realism elements in Gareth Brown’s The Book of Doors. The objective of this study is to analyze the use of magical realism by identifying the five primary features of magical realism within the novel’s plot, characters, and setting. In answering the problem of the statement, this study uses new criticism literary approach and Wendy B. Faris’ theory of magical realism. This study uses descriptive qualitative as the research design, focusing on textual analysis by interpreting specific quotations. The novel, The Book of Doors by Gareth Brown serves as the data source for this study. The result shows that all five elements of magic realism can be found in the novel. The irreducible element can be found throughout the story with the existence of magical books, primarily the Book of Doors and the Book of Shadows. The phenomenal world is proven with how familiar the settings and the activity in the story that resembles the real world, for example, the social gap between Cassie and her employer. Unsettling doubt appears as characters and readers question the boundary between reality and magic. Merging realm is shown through the natural coexistence of the ordinary world and the shadow realm. Lastly, characters are able to roam across time and space using the ability of the Book of Doors, reflecting the disruption of identity, time, and space.